2020
DOI: 10.1186/s12889-020-09629-x
|View full text |Cite
|
Sign up to set email alerts
|

Tickborne disease awareness and protective practices among U.S. Forest Service employees from the upper Midwest, USA

Abstract: Background People with occupations that require them to spend time working outdoors in suitable tick habitats are predicted to be at an increased risk for tick-borne diseases (TBDs). However, few studies have assessed the risks of outdoor employees in the United States. Methods We conducted a cross-sectional survey to collect data on exposure to ticks and TBD infections among U.S. Forest Service employees in a high TBD incidence regi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 38 publications
(56 reference statements)
0
12
1
Order By: Relevance
“…The proportion of participants planning to perform tick surveillance did increase from 15 to 20%, which was not statistically significant. There are conflicting reports on the effectiveness of increasing knowledge to promote preventative practices, but in the case of this study a significant association was not observed [ 27 , 30 , 33 , 34 ]. The lack of significant changes in practices may be related to some of the limitations of our study.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…The proportion of participants planning to perform tick surveillance did increase from 15 to 20%, which was not statistically significant. There are conflicting reports on the effectiveness of increasing knowledge to promote preventative practices, but in the case of this study a significant association was not observed [ 27 , 30 , 33 , 34 ]. The lack of significant changes in practices may be related to some of the limitations of our study.…”
Section: Discussioncontrasting
confidence: 81%
“…At least 80% of participants believed that TBDs were a public health problem, and over 70% indicated it was a problem in their own jurisdiction. High perceived risk of tick-borne diseases, such as that observed in our study, has been associated with increased willingness to perform preventive practices [ 27 , 29 , 30 ]. This was further confirmed by the significant positive correlation between perceived risk and perceived need for surveillance in our study following training.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In line with these findings, prior studies also indicated a high prevalence of tick bites among forestry workers. It was found that forestry workers had a high seroprevalence of LB and other tick-borne diseases (TBD) as well as a background of high tick exposure at work and a self-reported history of TBD [ 33 36 ]. Since ticks are not only common in forests, the slightly lower risk for farmers could be attributed to modern agricultural methods with tall machinery that lead to less encounters with ticks attached to crops.…”
Section: Discussionmentioning
confidence: 99%
“…However, in order to be properly considered a “cascade”, the training developed lacks two main elements: knowledge evaluation (quality control, ideally ongoing, to determine trainer/trainee performance, teaching quality, knowledge retention and changes in behaviour), and network sustainability (ensuring long-lasting results with additional rounds of training) [ 68 ]. For instance, ambassadors could have been asked to complete a pre-test and post-test to evaluate their knowledge prior to and after workshops using a knowledge, attitudes, and practices study, and a similar assessment could have been done with their own trainees [ 69 ]. Making sure ambassadors and their trainees are able to make waves of their own with the proper information would ensure this program is solid and that it can be effective in the long-term.…”
Section: Discussionmentioning
confidence: 99%